Association between media exposure and family planning in Myanmar and Philippines: evidence from nationally representative survey data - Pranta Das; Nandeeta Samad; Hasan Al Banna; Temitayo Eniola Sodunke; John Elvis Hagan; Bright Opoku Ahinkorah; Abdul-Aziz Seidu (BMC, 2021)
Abstract Background Although women in South Asia and South-east Asia have developed their knowledge regarding modern contraceptive and other family planning techniques, limited information exists on the influence of mass media exposure on the utilization of contraceptives and family planning. The current study examined the association between media exposure and family planning in Myanmar and Philippines. Methods The study analyzed data from the 2017 Philippines National Demographic and Health Survey (NDHS) and 2015-16 Myanmar Demographic and Health Survey (MDHS). Three family planning indicators were considered in this study (i.e., contraceptive use, demand satisfied regarding family planning and unmet need for family planning). A binary logistic regression model was fitted to see the effect of media exposure on each family planning indicator in the presence of covariates such as age group, residence, education level, partner education level, socio-economic status, number of living children, age at first marriage, and working status. Results The prevalence of contraception use was 57.2% in the Philippines and 55.7% in Myanmar. The prevalence of demand satisfied regarding family planning was 70.5 and 67.1% in the Philippines and Myanmar respectively. Unmet need regarding family planning was 16.6% and 19.9% in the Philippines and Myanmar respectively. After adjusting for the covariates, the results showed that women who were exposed to media were more likely to use contraception in Philippines (aOR = 2.24, 95% CI = 1.42-3.54) and Myanmar (aOR 1.39, 95% CI = 1.15-1.67). Media exposure also had a significant positive effect on demand satisfaction regarding family planning in the Philippines (aOR = 2.19, 95% CI = 1.42-3.37) and Myanmar (aOR = 1.34, 95% CI = 1.09-1.64). However, there was no significant association between media exposure and unmet need in both countries. Conclusions The study established a strong association between mass media exposure and the use and demand satisfaction for family planning among married and cohabiting women in Philippines and Myanmar. Using mass media exposure (e.g., local radio, television- electronic; newspapers) to increase both access and usage of contraceptives as well as other family planning methods in these countries could be pivotal towards the attainment of United Nations Sustainable Development Goal 3 (SDG 3) of improving maternal health.